The Influence of Digital Literacy and Entrepreneurial Behavior on Small Business Performance (Study on Culinary Business in Jeneponto Regency) - Nur Samsul Bahri, Nur Samsul Bahri; Muhammad Rakib; Muhammad Ihsan Said Ahmad; Rahmatullah; Muhammad Hasan (Daengku: Journal of Humanities and Social Sciences Innovation, 2021)
Using Jeneponto Regency's culinary businesses as a case study, this study tries to investigate whether digital literacy and entrepreneurial behavior have an impact on business performance. Business performance is the dependent variable in this study. The independent factors in this study include digital literacy and entrepreneurial behavior. Using quantitative descriptive research and correlational methods, this study examines the relationship between the two variables. 307 culinary enterprises registered with the Jeneponto Regency Department of Cooperatives and SMEs comprised the study's population, from which a sample of 39 culinary firms was selected. Observing, documenting, and distributing questionnaires were used to collect data (questionnaires). Descriptive statistical analysis and inferential statistics are employed in the analysis process. Digital Literacy (X1) and Entrepreneurial Behavior (X2) had a good and significant effect on the success of small enterprises (Y) in culinary businesses in Jeneponto Regency, according to the study results. Because of its greater regression coefficient value than digital literacy, entrepreneurial activity is the most influential variable in this study.